Relationship of the Herzberg’s Dual Factor Theory with Job Satisfaction and Motivation of Science Teachers - Sadia Batool, Muhammad Shahnawaz, Shomaila Habib (JSE, 2023)
The study was conducted on the implications of Herzberg’s two-factor theory on the job satisfaction of high school science teachers of district Rawalpindi, Pakistan. It explored the effect of the influence of Herzberg’s motivational factors and hygiene factors on the job satisfaction of science teachers and the effect of each sub-factor on their job satisfaction. The relationship of sub-factors with respect to gender and area was also explored in this study.